The role of mood disorders in the longitudinal course of obsessive-compulsive disorder: Preliminary data from a 20-year prospective follow-up study. (13th April 2021) - Bramante, S.; Borsotti, A.; Rigardetto, S.; Maina, G.
Abstract : Introduction: Although OCD is believed to have a chronic course, little research has been conducted on this, and there are discrepant findings. Studies over the last years have found that a significant proportion of patients with OCD shows symptomatic remission over long term, however there are significant variations in sampling, clinical characteristics, follow-up, and outcome assessments. Objectives: The present prospective study aims to examine rates of OCD remission after 20 years of follow up and to explore demographic and clinical predictors of remission. Methods: The study sample consists of adult patients with a principal OCD diagnosis and Y-BOCS total score ≥16, who have been referred to the Department of Neuroscience, University of Turin (Italy). OCD symptoms were assessed every 5 years over the 20-year follow-up period. Course data were examined using standard survival analysis methods; Cox proportional hazards regression was used to estimate relative hazards for predictors of remission. Results: There were 360 participants in the study. At year 20, the 28.7 % of the total sample showed OCD remission. Predictor of remission were female gender, lower Y-BOCS mean scores at study entry, longer duration of illness and comorbidity with major depressive disorder. No specific predictors of full remission were found. Lower Y-BOCS mean scores and comorbid bipolar disorder predicted partial remission. Conclusions: This study suggests that a significant proportion of patients with OCD shows remission. Future studies are needed to clearly identify predictors of remission. Disclosure: No significant relationships.